A Philosophical Analysis of Neuroenergetics - Shulman, Robert (Frontiers in Neuroenergetics, 2011)
Neuroimaging studies measure cerebral rates of glucose and oxygen consumption yet they are often interpreted to support philosophical positions about mental processes presumed to represent behavior. Cognitive Neuroscience has claimed that Neuroimaging resolves Descartes’ dualism of Mind and Matter by mapping such presumed mental processes onto the brain. Bennett & Hacker point out that this is nonsense because a person, not the brain, performs observable activities such as remembering, planning or voting. This analysis is supported by the continuing inability of neuroimaging to locate the modular brain activities postulated to perform mental activity. Pragmatist philosophy emphasizes that such postulated representations are contingent hypothesis invented to deal with the world in everyday life and are not definable as proposed by Cognitive Neuroscience. A recent philosophy of Mechanisms, reflecting what biologists actually do when explaining observable phenomena, looks for explanations not from postulated representations but from multi-level, multi-disciplinary mechanisms of metabolism and energetics which are actually measured in neuroimaging. The value of this philosophy is illustrated by the experimental relations between cerebral energetics in disorders of consciousness and the response to stimuli.